TRANSITION TO THE MARKET ECONOMYAND THE CHANGES IN THE EDUCATION: THE CASE OF THE BALTIC STATES AND LATVIA IN PARTICULAR - Baiba Savrina (European Scientific Journal, ESJ, 2014)
The paper is analyzing main characteristics of the education development in 3 Baltic States throughout 3 periods: National independence period between two World Wars, Soviet period and restitution of National States. The theories of human capital are used to explain the attitude to the education. The role of universities during the transition to market economy was changed. The professional changes in labor market can be observed. The education and the qualification are the necessary preconditions of competitiveness.